Cutting parameter optimisation for aluminium LM6 composite using experimental design - Yusuf, Muhammad (2013)
The purpose of metal cutting operations such as a machining process is to produce a part of the required shape and dimensions with the specified quality and surface finish. A comprehensive understanding of the cutting process is required to determine optimum cutting conditions which enable the machining of new generation materials such as alloys and metal matrix composites, which are often more difficult to machine due to the pursuit of improved product properties and improved dimensional accuracy of machined products. The Machinability of a material is should always be considered in conjunction with the machining method, the cutting tool, and the machining parameters. The materials have excellent machinability required little power to cut, longer tool life and good surface finish. Machinability can be difficult to predict because machining has so many variables. Optimisation of cutting parameters is the most common strategy to improve the machinability of the materials. Therefore, selection of cutting parameters such as cutting speed, feed rate and depth of cut are important for optimum machining performance. The inappropriate selection of combination cutting parameter will lead to bad cutting condition e.g. vibration that affects the surface finish. Different workpiece material with different property and microstructure give different effect to the surface condition and the cutting tool performance. This research intended to optimisation cutting condition with three principal cutting parameters which are cutting speed, feed rate and depth of cut based on the surface roughness,tool wear and chip formation during turning process under wet and dry cutting conditions. The cutting parameters are selected based on design of experiment method. Results show that there are various differences in surface roughness between wet and dry cutting process with the applied similar cutting parameter model during machining of mild steel material. Surface roughness values of AA7050 aluminium alloy is found to be lower as compared to surface roughness values of LM6 alloy in the similar of cutting condition model. Surface roughness values of titanium carbide particles reinforced LM6 aluminium composite are higher as compared to LM6 aluminium alloy at similar cutting condition. This indicates that the machined surface quality is depending on the structures and constituents of the workpiece materials. The chip forms produced during turning of aluminium alloys and aluminium-titanium carbide composite at similar of cutting condition is found the different of shape. The chip characteristics of these materials are found continuous and noncontinuous shape. This is due to the chip forms depending on the constituent and the properties of the workpiece materials. Turning operation at high cutting speed of 250 m min-1 produced faster tool wear as compared to low cutting speed of 175 m min-1 and 100 m min-1 during cutting of 2 wt.% titanium carbide particles reinforced LM6 aluminium using uncoated carbide tool. The flank wear progression increases rapidly at high depth of cut and feed rate, 1.5 mm and 0.2 mm rev-1, respectively.